2011
DOI: 10.1001/archoto.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

Injection Medialization Laryngoplasty in Children

Abstract: This study supports injection laryngoplasty as a safe and effective intervention for children with glottic insufficiency. Further prospective studies are necessary to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Importantly, many of the studies done on this subject focus on the impact of dysphonia rather than dysphagia associated with UVFI. Swallowing dysfunction should not be overlooked, however, because reflux disease, feeding difficulties, and choking are commonly exhibited symptoms in affected children .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, many of the studies done on this subject focus on the impact of dysphonia rather than dysphagia associated with UVFI. Swallowing dysfunction should not be overlooked, however, because reflux disease, feeding difficulties, and choking are commonly exhibited symptoms in affected children .…”
Section: Discussionmentioning
confidence: 99%
“…Of these options, IL is the only one indicated for potentially reversible UVFI because the procedure can be performed with a temporary injectate that reabsorbs over time. IL has historically been performed less often in children than in adults, in part because of concerns regarding the potential for airway obstruction due to the smaller size of the pediatric larynx . In recent years, there has been an increasing interest in IL to improve symptoms of aspiration with feeding, facilitate return to a normal diet, and potentially obviate the need for a gastrostomy tube (G‐tube).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the presence of vocal cord dysfunction is the first step in directing subsequent therapy, including surgical intervention as medialization of the affected vocal cord has been shown to reduce the rate of pneumonia and length of stay. 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…Totally 50 reported were collected, including 19 (38%) case reports or case series [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], 1 (2%) technique [30], 17 (34%) retrospective [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 13 (26%) prospective reports [7,11,[49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-six percent of the patients required surgical intervention, including injection into the paralyzed fold and medialization thyroplasty [4]. Gelfoam, radiesse voice, and radiesse voice gel injections in patients with hoarseness led to improvement in 94% [48]. Joo et al [47] reported that injection laryngoplasty or medialization thyroplasty were applied in all three of their patients with permanent vocal cord paralysis.…”
Section: Managementmentioning
confidence: 99%